Associations of blood pressure and arterial stiffness with knee cartilage volume in patients with knee osteoarthritis. (5th February 2021) - Wang, Yuanyuan; Meng, Tao; Ruan, Guangfeng; Zheng, Shuang; Zhu, Jimin; Cen, Han; Antony, Benny; Wluka, Anita E; Cicuttini, Flavia; Winzenberg, Tania; Pelletier, Jean-Pierre; Martel-Pelletier, Johanne; et al.
Abstract: Objective: To describe the associations of blood pressure and arterial stiffness with knee cartilage volume in patients with knee OA. Methods: A secondary analysis was performed on the data from participants in a randomized controlled trial that identified the effects of vitamin D supplementation on knee structures and symptoms among patients with symptomatic knee OA. Brachial and central blood pressure, arterial stiffness indicators and knee cartilage volume were measured at baseline and the 2 year follow-up. Associations were assessed using generalized estimating equations. Results: Among 231 participants (average age 63.2 years), 48.9% were females. Higher supine systolic and diastolic pressures were significantly associated with lower tibial cartilage volume (systolic: lateral β −6.23, medial β −5.14, total β −11.35 mm 3 /mmHg; diastolic: lateral β −10.25, medial β −11.29, total β −21.50 mm 3 /mmHg). Higher supine systolic pressure was associated with lower femoral cartilage volume (lateral β −17.35, total β −28.31 mm 3 /mmHg). Central systolic pressure and arterial stiffness indicators (including pulse wave velocity, central pulse pressure and peripheral pulse pressure) were largely not associated with knee cartilage volume; however, higher augmentation index was associated with lower tibial and femoral cartilage volume (tibial: medial β −8.24, total β −19.13 mm 3 /%; femoral: lateral β −23.70, medial β −26.42, total β −50.12 mm 3 /%). Conclusions: Blood pressure and arterial stiffness are associated with knee cartilage volume at several sites in knee OA patients. This supports that blood pressure and arterial stiffness may involve in the progression of knee OA.